2020
DOI: 10.1177/1591019920923831
|View full text |Cite
|
Sign up to set email alerts
|

Association of local anesthesia versus conscious sedation with functional outcome of acute ischemic stroke patients undergoing embolectomy

Abstract: Purpose Compare functional outcomes of acute ischemic stroke patients undergoing embolectomy with either local anesthesia or conscious sedation. Secondarily, identify differences in hemodynamic parameters and complication rates between groups. Materials and methods Single institution, retrospective review of all acute ischemic stroke patients undergoing embolectomy between January 2014 and July 2018 ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Whilst there is evidence that blood pressure (BP) drops are associated with poor functional outcome due to collateral failure 26,27 ; the neurotoxic or neuroprotective effects of hypnotic agents and optimal intra-and peri-procedural BP targets during the acute ischaemiareperfusion injury are incompletely understood 28 . Of note, in the present analysis, only one of the included studies reported intra-procedural BP measurements and found no statistical differences in their selected haemodynamic parameters 18 .…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Whilst there is evidence that blood pressure (BP) drops are associated with poor functional outcome due to collateral failure 26,27 ; the neurotoxic or neuroprotective effects of hypnotic agents and optimal intra-and peri-procedural BP targets during the acute ischaemiareperfusion injury are incompletely understood 28 . Of note, in the present analysis, only one of the included studies reported intra-procedural BP measurements and found no statistical differences in their selected haemodynamic parameters 18 .…”
Section: Discussionmentioning
confidence: 49%
“…Unsurprisingly, due to the logistics of anaesthetic induction and intubation, we found significantly shorter door-to-groin puncture times in the LA group compared to the GA group, which was also shown to favour LA versus CS in the single study reporting on this metric 18 . No statistical difference was identified in groin puncture-to-reperfusion times in the LA vs GA comparison (±SD, minutes) 52.5±31.8 and 56.0±34.5 respectively.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Немає однозначної думки щодо застосування певних методів анестезії МТЕ. Декілька років тому вважали, що краще проводити МТЕ під загальною анестезією, потім виник інтерес до седації та місцевої анестезії, останніми роками у багатьох джерелах віддають перевагу методу загальної анестезії, аргументом на його користь є віддалені результати МТЕ [5][6][7][8][9][10][11][12].…”
unclassified